The West and Their Undermining of Freedoms: The Islamic Hijab as a Model - A Contemporary Intellectual Study - Abdul Wahid, Shukriya H. (PROSPECTIVE RESEARCHES, 2025)
In the Name of Allah, the Most Gracious, the Most Merciful. Praise be to Allah, Lord of the Worlds, and peace and blessings be upon our Prophet Muhammad (peace and blessings be upon him and his family), his chosen companions, and those who follow them until the Day of Judgment. This study highlights that Islam, as the divine religion, is the only system that has placed women in their rightful position and granted them full rights, rights that had been denied to them in pre-Islamic societies and even in many post-Islamic ones. The research emphasizes that the concept of hijab is a religious obligation in Islam and asserts that personal freedom is guaranteed and encouraged within Islamic teachings. However, such freedoms are bound by the limits set by Islamic law, as stated in the Qur'an: “It is not for a believing man or a believing woman, when Allah and His Messenger have decided a matter, that they should [thereafter] have any choice about their affair. And whoever disobeys Allah and His Messenger has certainly strayed into clear error.” (Surah Al-Ahzab: 36), Those who choose Islam as their faith accept servitude to Allah, abiding by His commands and respecting His boundaries. The study underscores that hijab is essential for women to preserve their dignity and fulfill their role in society. It concludes that Western nations, despite their claims to uphold personal freedoms, contradict their own principles by imposing restrictions on Muslim women living in these countries, denying them the right to adhere to their religious beliefs and practices.